If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(5s+1)-6s=3(3s+6)-23
We move all terms to the left:
3(5s+1)-6s-(3(3s+6)-23)=0
We add all the numbers together, and all the variables
-6s+3(5s+1)-(3(3s+6)-23)=0
We multiply parentheses
-6s+15s-(3(3s+6)-23)+3=0
We calculate terms in parentheses: -(3(3s+6)-23), so:We add all the numbers together, and all the variables
3(3s+6)-23
We multiply parentheses
9s+18-23
We add all the numbers together, and all the variables
9s-5
Back to the equation:
-(9s-5)
9s-(9s-5)+3=0
We get rid of parentheses
9s-9s+5+3=0
We add all the numbers together, and all the variables
8!=0
There is no solution for this equation
| 7(2-x)=4x+8 | | 7(2-x=4x+8 | | 7(2-2x)=4x+8 | | 2(2x+3)+4(5+x=22) | | x+6=5/2 | | 0.70+0.05(20-x)=0.10(114) | | 5x7-5x1/5=34 | | x+8/2=18 | | 90+0.5x=x | | (6x-28)-(x+34)=45 | | 5(x+3)-4=12 | | 3/2x2/3=1 | | x+3/4-x+4/6=x/2-2 | | 14+5x=3x-2 | | 12(x+3)=3(4x+3)+27 | | w+1/2=-5/8 | | (x+5)/2=11 | | 3x-1=9x=3 | | 4x+2(4-2(-+2))=2x-4 | | 5x+4-2x=6 | | 4⋅(x+1)=2x+10= | | -7.3k=3.7k-2.2 | | 4(4x-2)=2(8x+3) | | 3x+4x-8=22 | | 4m-3÷7=3 | | 0.6x−0.2(3−x)=4.6 | | 0.16(y-8)+0.14y=0.10y-1 | | 0.18(y-3)+0.06y=0.04y-1.5 | | |1-2/3x|=-3 | | X+x+1+1/4=100 | | -4y-11=3y+24 | | -10=6t-28 |